Transcriptomic analysis of in vivo and in vitro produced bovine embryos revealed a developmental change in cullin 1 expression during maternal-to-embryonic transition - Kepkova, K Vodickova; Vodicka, P; Toralova, T; Lopatarova, M; Cech, S; Dolezel, R; Havlicek, V; Besenfelder, U; Kuzmany, A; Sirard, M-A; Laurincik, J; Kanka, J (Theriogenology, 2011)
Pre-implantation embryos derived by in vitro fertilization differ in their developmental potential from embryos obtained in vivo. In order to characterize changes in gene expression profiles caused by in vitro culture environment, we employed microarray constructed from bovine oocyte and preimplantation embryo-specific cDNAs (BlueChip, Université Laval, Québec). The analysis revealed changes in the level of 134 transcripts between in vitro derived (cultured in COOK BVC/BVB media) and in vivo derived 4-cell stage embryos and 97 transcripts were differentially expressed between 8-cell stage in vitro and in vivo embryos. The expression profiles of 7 selected transcripts (BUB3, CUL1, FBL, NOLC1, PCAF, GABPA and CNOT4) were studied in detail. We have identified a switch from Cullin 1-like transcript variant 1 to Cullin 1 transcript variant 3 (UniGene IDs BT.36789 and BT.6490, respectively) expressions around the time of bovine major gene activation (8-cell stage). New fibrillarin protein was detected by immunofluorescence already in early 8-cell stage and this detection correlated with increased level of fibrillarin mRNA. The qRT-PCR analysis revealed significant differences in the level of BUB3, NOLC1, PCAF, GABPA and CNOT4 gene transcripts between in vivo derived (IVD) and in vitro produced (IVP) embryos in late 8-cell stage. The combination of these genes represents a suitable tool for addressing questions concerning normal IVD embryo development and can be potentially useful as a marker of embryo quality in future attempts to optimize in vitro culture conditions.
Keywords: sekvenční seřazení; Blastocyst; sekvence nukleotidů; embryonální vývoj; kulinové proteiny; Molecular Sequence Data; Embryo Culture Techniques; molekulární sekvence - údaje; kultivace embrya; zvířata; Culture Media; kultivační média; Cullin Proteins; Gene Expression Regulation, Developmental; blastocysta; Embryonic Development; Cattle; Base Sequence; stanovení celkové genové exprese; skot; vývojová regulace genové exprese; Animals; Gene Expression Profiling; Sequence Alignment